Simulating renewal: Postwar technopolitics and technological urbanism. (December 2020) - Elrick, John W
This article traces the terms and practices underwriting emergent forms of urban government to technical efforts to simulate markets after the Second World War. With an eye toward contemporary techno-utopian schemes and city-building initiatives, I argue that the basis of technological approaches to urban rule today—a conception of cities as complex socio-economic systems amenable to market-driven optimization—was forged by postwar administrators and technicians in response to the vicissitudes of uneven development. To advance this claim, I examine the history of San Francisco's Community Renewal Program, an early modeling initiative sponsored in the US by the federal government. After situating it in the context of racialized housing markets and policies, I probe the Community Renewal Program's attempt to build a computer model capable of forecasting the effects of redevelopment on housing markets. Though the Community Renewal Program model ultimately proved unviable as a planning tool, expert appraisals of it at the time simultaneously confirmed the characterization of cities as systems of market signals and affirmed in principle the ability to model and thus manage them given an appropriate technological infrastructure. In this light, current municipal design and development projects premised on interactive and remote-sensing technologies express something of the technocratic politics and optimism of the mid-20th century.